Complications of lung transplantation on computed tomography: pictorial essay - Gonçalves,Dâmaris Versiani Caldeira (2022)
Abstract Lung transplantation is becoming increasingly more common as an alternative treatment for end-stage lung disease. Despite advances in laboratory testing, surgical technique, and donor/recipient selection, lung transplantation is still associated with significant mortality, due to postoperative complications. This paper consists of a brief review of postoperative complications in lung transplant recipients, illustrating those complications with computed tomography images.